2012
DOI: 10.1164/rccm.201203-0465pp
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Effusion

Abstract: Malignant pleural effusion (MPE) poses a significant clinical problem. Current non-etiologic management is suboptimal in terms of efficacy and safety. In light of recent research progress, we propose herein a new view of MPE development, which may rapidly translate into meaningful changes in therapeutics. In addition to tumor-induced impairment of pleural fluid drainage, pertinent findings point towards another pathway to MPE formation: a vicious loop of interactions between pleural-based tumor cells and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 48 publications
1
78
0
Order By: Relevance
“…The evaluation was performed according to the evaluation criteria established by Cochrane Handbook (Version 5.0.1) [28]. As shown in Table 3, the results showed that 4 of the 13 studies (30.7 %) belonged to the low risk of bias [17, 20, 24, 27], and the rest [1, 4, 5, 810, 15, 16, 18, 19, 21–23, 25, 26, 29] were inclined to indicate an unclear risk of bias (69 %) (Table 3). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation was performed according to the evaluation criteria established by Cochrane Handbook (Version 5.0.1) [28]. As shown in Table 3, the results showed that 4 of the 13 studies (30.7 %) belonged to the low risk of bias [17, 20, 24, 27], and the rest [1, 4, 5, 810, 15, 16, 18, 19, 21–23, 25, 26, 29] were inclined to indicate an unclear risk of bias (69 %) (Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…However, most of lung cancer cases are often resistant to standard chemotherapy agent, or eventually become chemoresistant. Therefore, the fact is many chemotherapeutic agents are not as effective as we expected in treating MPE via thoracic perfusion [4]. Today, novel molecular targeted drugs that have been studied to improve the cure and control rate of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…PE is responsible for indirectly influencing tumor cells, regulating inflammation and contributing to tumor dissemination. 19 The population of CD14 C cells in the tumor microenvironment consists of tumor-associated macrophages (TAM) and monocytes. In mesothelioma, M2 macrophages with immunosuppressive features have been observed in the tumor; their ratio (CD163/ CD68) having a negative prognostic value.…”
Section: Introductionmentioning
confidence: 99%
“…MPE manifests with vascular leakiness that leads to fluid accumulation in the pleural space and is etiologically associated with fulminant inflammation and neovascularization, rather than mere tumour-induced lymphatic obstruction2. However, the reason why some patients with pleural tumours develop MPE while others do not remains unknown3.…”
mentioning
confidence: 99%